Performance of colour fidelity metrics. (December 2015) - Dangol, R; Bhusal, P; Halonen, L
To investigate the performance of three different colour fidelity metrics, Commission Internationale de l'Eclairage (CIE) colour-rendering index (CRI), colour quality scale (CQS) and CRI2012, lighting booth experiments were conducted. Three different light-emitting diode spectral power distribution, all at correlated colour temperatures of 2800 K, 4000 K and 6500 K, were simulated for Ra > 90, Ra ≈ 80 and Ra < 60. It was found that CIE CRI, CQS and CRI2012 were highly correlated with visual colour difference. It was also found that colour quality scale provides better prediction for the light-emitting diode light source that highly increases object chroma. However, more colour fidelity experiments using light-emitting diode light sources that highly increase object chroma are required before recommending any final colour fidelity metric.